Sun, shade and natural daylight in South African town planning, with emphasis on Pretoria - Conradie, Dirk (University of the Free State, 2018)
A bioclimatic analysis of different South African towns and cities indicates that, if the correct mix of passive design principles is used, they all have a significant passive design potential. Of all such measures, solar protection and shading is the single most important passive design measure to reduce energy usage and to improve internal comfort for buildings in all South African climatic regions. The correct design of public open spaces and streets facilitates, to a great extent, energy-efficient buildings, whilst at the same time providing functional and comfortable urban open spaces and streets. Passive solar buildings aim to maintain interior thermal comfort throughout the sun’s diurnal and annual cycles, whilst reducing the requirement for active heating and cooling systems. The aim of this article is to investigate the effect of climate zones on passive design potential, of which shading design is an integral part, using Pretoria as a case study. This includes the effect of street width, building height, street layout, orientation, and the amount of sunlight available for trees and plants in the urban environment. The Spatial Planning and Land Management Act (2013), City of Tshwane Land Use Management By-law (2016) and the Tshwane Town-Planning Scheme 2008 (Revised 2014) were used as regulatory framework. To support the research, an Early Design Phase (EDP) experimental research platform was used to investigate the amount of sunlight on building facades with different orientations. This method enables the calculation of shading angles where there is a balance between the hot periods (requiring cooling) and cool periods (requiring heating) from the urban and building perspective. This has been achieved by means of the development of analytical software that uses weather files as one of the inputs to calculate critical solar angles. Over and above the calculation of current building solar protection angles, this method also facilitates the calculation of the increase in solar protection that will be required with climate change such as with the expected A2 climate change scenario (business-as-usual scenario) for South Africa. To support the EDP analysis, detailed simulations were also undertaken by means of Ecotect v5.60.
Keywords: Cities; Climate change; Natural daylight; Shade; Sun; South Africa